TINJAUAN YURIDIS TINDAK PIDANA PENGANIAYAAN BERENCANA YANG DIPUTUS PASAL 351 AYAT 2 KUHP (PUTUSAN NOMOR 155/PID.B/2021/PN KDL): Juridical Review Of The Planned Criminal Action Decisioned Article 351 Paragraph 2 Of The Criminal Code (Decision Number 155/Pid.B/2021/Pn Kdl) - Bastari, Fuad Ahil; Tawang, Dian Adriawan Daeng (AMICUS CURIAE, 2024)
The title of this research is "Legal Analysis of the Crime of Persecution Planned in Decision Number 155/Pid.B/2021/PN Kdl". This research aims to evaluate whether the actions of the accused, Beni Agus Tono Bin Mundakir, can be considered premeditated maltreatment according to the Criminal Code's Article 353 Paragraph 2. Additionally, the judges' perspectives on this case's legal aspects will be discussed. The research is conducted using a normative approach and descriptive analysis method. Secondary sources, primarily literature studies, are utilized as data sources. The analysis concludes that the accused's actions do not fully meet the criteria for severe maltreatment according to Article 351 Paragraph 2 of the Criminal Code. However, they are more appropriate to be classified as premeditated maltreatment resulting in serious injury according to Article 353 Paragraph 2 of the Criminal Code, based on the legal facts and requirements during the trial process.